2017
DOI: 10.1186/s40677-017-0073-1
|View full text |Cite
|
Sign up to set email alerts
|

Spaceborne, UAV and ground-based remote sensing techniques for landslide mapping, monitoring and early warning

Abstract: Background: The current availability of advanced remote sensing technologies in the field of landslide analysis allows for rapid and easily updatable data acquisitions, improving the traditional capabilities of detection, mapping and monitoring, as well as optimizing fieldwork and investigating hazardous or inaccessible areas, while granting at the same time the safety of the operators. Among Earth Observation (EO) techniques in the last decades optical Very High Resolution (VHR) and Synthetic Aperture Radar (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
146
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 268 publications
(181 citation statements)
references
References 155 publications
2
146
0
3
Order By: Relevance
“…Landslide event mapping is a wellknown activity obtained through field surveys (Yoon et al, 2012;Santangelo et al, 2010), visual interpretation of aerial or satellite images (Brardinoni et al, 2003;Ardizzone et al, 2013) and combined analysis of lidar DTM and images (Van Den Eeckhaut et al, 2007;Haneberg et al, 2008;Giordan et al, 2013;Razak et al, 2013;Niculiţa, 2016). The use of RPASs for the identification and mapping of a landslide has been described by several authors (Niethammer et al, , 2010(Niethammer et al, , 2011Rau et al, 2011;Carvajal et al, 2011;Travelletti et al, 2012;Torrero et al, 2015;Casagli et al, 2017). Niethammer et al (2009) and Liu et al (2015) showed how RPASs could be considered a good solution for the acquisition of ultra-high-resolution images with low-cost systems.…”
Section: Landslide Recognitionmentioning
confidence: 99%
“…Landslide event mapping is a wellknown activity obtained through field surveys (Yoon et al, 2012;Santangelo et al, 2010), visual interpretation of aerial or satellite images (Brardinoni et al, 2003;Ardizzone et al, 2013) and combined analysis of lidar DTM and images (Van Den Eeckhaut et al, 2007;Haneberg et al, 2008;Giordan et al, 2013;Razak et al, 2013;Niculiţa, 2016). The use of RPASs for the identification and mapping of a landslide has been described by several authors (Niethammer et al, , 2010(Niethammer et al, , 2011Rau et al, 2011;Carvajal et al, 2011;Travelletti et al, 2012;Torrero et al, 2015;Casagli et al, 2017). Niethammer et al (2009) and Liu et al (2015) showed how RPASs could be considered a good solution for the acquisition of ultra-high-resolution images with low-cost systems.…”
Section: Landslide Recognitionmentioning
confidence: 99%
“…This approach allows selecting not only the point-wise coherent scatterers (PS) but also the DS (distributed scatterers) points that typically correspond to homogeneous areas as bare soils or non-cultivated areas. The use of this type of analysis allows considerably increasing the number of measurement points (MP) in areas with low urban density, as in the proposed case study (Bellotti et al 2014;Notti et al 2014;Bianchini et al 2015a, b;Casagli et al 2017;Raspini et al 2017). Ferretti et al (2011) reported that the SqueeSAR algorithm is able to increase of one order of magnitude the number of MP, enhancing at the same time the signal-to-noise ratio of the single measurement and so improve the quality of the time series.…”
Section: Squeesar Analysismentioning
confidence: 99%
“…In this context, the availability of new remote sensing technologies, based primarily on satellite, aerial and terrestrial remote sensing platforms, can allow systematic and easily updatable acquisitions of data over wide areas, and therefore may improve the production of landslide maps, reduce costs and optimize field work [2,3]. In recent years, amongst the new methods for accurate landslide mapping, ground-based technologies such as digital photogrammetry (DP) [4][5][6], terrestrial laser scanning (TLS) [7][8][9], ground-based interferometric synthetic aperture radar (GB-InSAR) [10][11][12] and infrared thermography (IRT) [13][14][15], have been increasingly used as efficient remote surveying techniques for the prompt characterization and mapping of slopes affected by instability processes.…”
Section: Introductionmentioning
confidence: 99%